Corporate governance and earnings management: A study on the Malaysian family and non-family Owned PLCs - Mansor, N. (Elsevier B.V., 2013)
This study supported the claim that corporate governance (CG) mechanisms are able to overcome earnings management (EM) activities specifically from the perspective of family owned companies (FOC) and the non-family owned companies (NFOC). A total sample of 264 public listed companies (PLCs), selected based on stratified samplings, were tested. The results showed that for FOC, only number of board meetings held; while for NFOC, independence of directors, audit committee, non-duality, audit committee size, in-house internal audit function and quality differentiated auditors are the CG mechanisms that are found to be able to assist in minimizing the EM activities.